JustModeling: An MDE Approach to Develop Android Business Applications - Freitas, Fabiano; Maia, Paulo Henrique Mendes (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2016: Anais do VI Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2016)
The continuous growth of the Android market has resulted in greater demand for applications and shorter development cycles. Developers and companies are adopting solutions to increase productivity and reduce development time and effort. Among them, Model-driven Engineering (MDE) has emerged as a concrete alternative to automatically generate Android applications. However, the current MDE propositions generate only part of the application, forcing developers to spend time in implementation tasks. To tackle that, we propose JustModeling, an MDE approach formed by JBModel, a graphical modeling tool with which the user models the application business classes using the UML class diagram and that provides a set of model transformations to generate code for the JustBusiness framework, which automatically generates all necessary resources of the mobile application. This allows developers to work on a higher level of abstraction, focusing on the application design rather than implementation issues. The approach was validated by a case study that showed better results than JustBusiness and the traditional development.